Catalytic Chemical Vapor Deposition : Technology and Applications of Cat-CVD - Matsumura, H. (Wiley-VCH, 2019)
The authoritative reference on catalytic chemical vapor deposition'written by the inventor of the technology This comprehensive book covers a wide scope of Cat-CVD and related technologies'from the fundamentals to the many applications, including the design of a Cat-CVD apparatus. Featuring contributions from four senior leaders in the field'including the father of catalytic chemical vapor deposition'it also introduces some of the techniques used in the observation of Cat-CVD related phenomena so that readers can understand the concepts of such techniques. Catalytic Chemical Vapor Deposition: Technology and Applications of Cat-CVD begins by reviewing the analytical tools for elucidating the chemical reactions in Cat-CVD, such as laser-induced fluorescence and deep ultra-violet absorption, and explains in detail the underlying physics and chemistry of the Cat-CVD technology. Subsequently it provides an overview of the synthesis and properties of Cat-CVD-prepared inorganic and organic thin films. The last parts of this unique book are devoted to the design and operation of Cat-CVD apparatuses and the applications.-Provides coherent coverage of the fundamentals and applications of catalytic chemical vapor deposition (Cat-CVD) -Assembles in one place the state of the art of this rapidly growing field, allowing new researchers to get an overview that is difficult to obtain solely from journal articles -Presents comparisons of different Cat-CVD methods which are usually not found in research papers -Bridges academic and industrial research'showing how CVD can be scaled up from the lab to large-scale industrial utilization in the high-tech industry Catalytic Chemical Vapor Deposition: Technology and Applications is an excellent one-stop resource for researchers and engineers working on or entering the field of Cat-CVD, Hot-Wire CVD, iCVD, and related technologies.